A questão da participação da comunidade do Distrito de Perus-(São Paulo/Brasil), no projeto MDL Aterro Bandeirantes - Carlos Alberto Rizzi (Confins)
From 2001 began the questioning of municipal government, civil society and experts about the future of the Aterro Bandeirantes, the world's largest landfill, located in a small district called Perus, in the western zone of São Paulo. Although the recommendation of experts and the will of the local community to create a park on the landfill, the municipal government has opted for an economic finality: the generation of electricity by burning methane gas emanating from the decomposition of accumulated junk. Since 2003, the municipal government, and Unibanco as chief mediator, came to encourage the deployment, in the landfill area, of a MDL – (Mechanism of Clean Development) project. This project is an instrument to operationalize the Kyoto Treaty for reduction of emission of pollutants into the atmosphere through the encouragement of economic practices that generate alternative energy, as the same time converting carbon credits (certified) in financial assets. The proposal would be a great idea for all the actors concerned, if the municipal authorities had not forgotten to call the local community to participate in the conduct of the project, something provided for in Article 2 of that Treaty. The following text is a statement of how was this process of dumping of local participation in the conduct of the project and on how was formed a monopoly of the hegemonic actors in the capture, generation, distribution and consumption of electricity generated, the lucrative Consórcio Bandeirantes, the aggregate of companies that gave rise to the Projeto MDL Aterro Bandeirantes.